Antagonistic activity of autosimbionts А. viridans, B. subtilis and their probiotic association to conditionally microflora - Stepansky D.A. (Medičnì Perspektivi, 2015)
In this research the data on examination of antagonist qualities of bioassotiantes A. viridans and strain B. subtilis 3 towards pathogenic and opportunistic pathogenic microflora isolated from oropharynx and nasopharynx of children who were in contact with patients with pulmonary tuberculosis (MBT +) are submitted. The expressed antagonist activity of autosimbionts A. viridans towards pathogenic and opportunistic pathogenic microflora was shown. Common antagonist activity of A. viridans (k) N 1 and B. subtilis 3 towards diverse strains of test-cultures is 1,5-2 times higher, than separate antagonist activity of A. viridans (k) №1 and B. subtilis 3. Received research data showed the possibility of continuing work on development of probiotic associations, that contain representatives of normal microflora - bioassociants A. viridans and probiotic strains B. subtilis 3 with broadspectrum of antagonistic activity in relation to the various groups of bacterium.